Health status and hypoglycaemia with insulin degludec versus insulin glargine: a 2‐year trial in insulin‐naïve patients with type 2 diabetes. Issue 9 (27th February 2014) - Rodbard, H. W.; Cariou, B.; Zinman, B.; Handelsman, Y.; Wolden, M. L.; Rana, A.; Mathieu, C.
<x xml:space="preserve">Abstract</x> Insulin degludec (IDeg) is a new basal insulin with an ultra‐long and stable glucose‐lowering effect. We compared once‐daily IDeg and insulin glargine (IGlar), both in combination with metformin ± dipeptidyl peptidase‐4 inhibitors, in a 52‐week, open‐label, treat‐to‐target trial in patients with type 2 diabetes followed by a 52‐week extension trial in which subjects [n = 725/1030 (70.4%)] maintained their initial randomised treatment. Health status was assessed at baseline and 105 weeks using the Short Form‐36 (SF‐36 v2) questionnaire. SF‐36 scores were analysed (ITT population) using anova, with adjustments for covariates. At 105 weeks, the overall physical component score was significantly better with IDeg versus IGlar [treatment contrast (TC): 1.1 (0.1; 2.1)95%CI, p < 0.05]. This was largely because of significantly better physical functioning [TC: 1.1 (0.0; 2.3)95%CI, p < 0.05] and bodily pain sub‐domain scores [TC: 1.5 (0.2; 2.9)95%CI, p < 0.05]. Improvements in health status with IDeg compared to IGlar were maintained after 2 years.